On the existence and uniqueness of solutions for a class of non-linear fractional boundary value problems - Arwa Ba Abdulla; Mohammed Al-Refai; Ahmed Al-Rawashdeh (Journal of King Saud University: Science, 2016)
In this paper, we extend the maximum principle and the method of upper and lower solutions to study a class of nonlinear fractional boundary value problems with the Caputo fractional derivative 1<δ<2. We first transform the problem to an equivalent system of equations, including integer and fractional derivatives. We then implement the method of upper and lower solutions to establish existence and uniqueness results to the resulting system. At the end, some examples are presented to illustrate the validity of our results.